2015
DOI: 10.1074/jbc.m115.646794
|View full text |Cite
|
Sign up to set email alerts
|

Kv4.2 and Accessory Dipeptidyl Peptidase-like Protein 10 (DPP10) Subunit Preferentially Form a 4:2 (Kv4.2:DPP10) Channel Complex

Abstract: Background: Kv4-DPP forms a complex of unknown stoichiometry. Results: Kv4.2-DPP10 current properties and stoichiometry are altered depending on their relative expression levels. Conclusion: The stoichiometry of Kv4.2-DPP10 is variable with a preference for the 4:2 configuration. Significance: Kv4-DPP stoichiometry may provide important information for the treatment of some psychiatric diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 66 publications
(87 reference statements)
1
10
0
Order By: Relevance
“…Considering that the concatemer containing a single silent subunit was functional, we should not exclude ad hoc the possibility of mixed populations. We demonstrated above that Kv2.1/Kv6.4 assemble predominantly in a 2:2 stoichiometry; however, it has been suggested previously that the expression-level ratio between compatible Kv subunits can influence the stoichiometry of heterotetrameric channel complexes in heterologous expression systems (22)(23)(24)(25)(26). Our results above may, thus, be a consequence of the ratio in which Kv2.1 and Kv6.4(-GFP) were expressed.…”
Section: Kv21/kv64 Channels Are Functional In a 3:1 Stoichiometricalmentioning
confidence: 45%
See 2 more Smart Citations
“…Considering that the concatemer containing a single silent subunit was functional, we should not exclude ad hoc the possibility of mixed populations. We demonstrated above that Kv2.1/Kv6.4 assemble predominantly in a 2:2 stoichiometry; however, it has been suggested previously that the expression-level ratio between compatible Kv subunits can influence the stoichiometry of heterotetrameric channel complexes in heterologous expression systems (22)(23)(24)(25)(26). Our results above may, thus, be a consequence of the ratio in which Kv2.1 and Kv6.4(-GFP) were expressed.…”
Section: Kv21/kv64 Channels Are Functional In a 3:1 Stoichiometricalmentioning
confidence: 45%
“…Other heterotetrameric Kv channels can assemble with a random subunit stoichiometry and arrangement, depending on the ratio between the involved subunits (22)(23)(24)(25)(26). For example, Kv7.2/Kv7.3 heterotetramers display a fixed 2:2 stoichiometry when cells express an equal amount of both subunits, but varying this ratio results in Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, recent studies have shown that DPP10 genetic variants affect lung function decline in ageing ( Poon et al, 2014 ), and have also been associated with aspirin-exacerbated respiratory disease ( Kim et al, 2015 ). DPP10 is a potassium channel-associated protein ( Chen et al, 2014 ; Kitazawa et al, 2015 ), but unlike other DPP family members, mammalian DPP10 lacks enzymatic activity and is unable to cleave terminal dipeptides from asthma-related cytokines and chemokines ( Allen et al, 2003 ). Interestingly, however, in Drosophila , DPP10 both acts as an ion channel substrate and has peptidase activity ( Shiina et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the widely studied KCNE subunits are transmembrane proteins that have been proposed to integrate into clefts between neighboring voltage-sensing domains to modulate channel function (Murray et al, 2016;Wang et al, 2012;Xu et al, 2013) . Another Kv channel with prominent regulation of channel gating by multiple classes of regulatory proteins is the Kv4 family, which is sensitive to both KChIP (a soluble cytoplasmic protein) and DPP-like proteins (transmembrane), leading to modulation of channel expression and gating (Jerng et al, 2005;Kitazawa et al, 2015;Zagha et al, 2005) . Although we have not yet collected direct Slc7a5 regulation of Kv1 channels evidence of an interaction between Slc7a5 and Kv1.1 or Kv1.2, our findings strongly suggest that Slc7a5 sensitivity is encoded by the voltage-sensing domains of these channels.…”
Section: Discussionmentioning
confidence: 99%